Acceptance and commitment therapy (ACT) for adult type 1 diabetes management: study protocol for a randomised controlled trial. Issue 11 (28th November 2018) - Amsberg, Susanne; Wijk, Ingrid; Livheim, Fredrik; Toft, Eva; Johansson, Unn-Britt; Anderbro, Therese
Abstract : Introduction: Integrating diabetes self-management into daily life involves a range of complex challenges for affected individuals. Environmental, social, behavioural and emotional psychological factors influence the lives of those with diabetes. The aim of this study is to evaluate the impact of a stress management group intervention based on acceptance and commitment therapy (ACT) among adults living with poorly controlled type 1 diabetes. Methods and analysis: This study will use a randomised controlled trial design evaluating treatment as usual (TAU) and ACT versus TAU. The stress management group intervention will be based on ACT and comprises a programme divided into seven 2-hour sessions conducted over 14 weeks. A total of 70 patients who meet inclusion criteria will be recruited over a 2-year period with follow-up after 1, 2 and 5 years. The primary outcome measure will be HbA1c . The secondary outcome measures will be the Depression Anxiety Stress Scales, the Swedish version of the Hypoglycemia Fear Survey, the Swedish version of the Problem Areas in Diabetes Scale, The Summary of Self-Care Activities, Acceptance Action Diabetes Questionnaire, Swedish Acceptance and Action Questionnaire and the Manchester Short Assessment of Quality of Life. The questionnaires will be administered via the internet at baseline, after sessions 4 (study week 7) and 7 (study week 14), and 6, 12 and 24 months later, then finally after 5 years. HbA1c will be measured at the same time points. Assessment of intervention effect will be performed through the analysis of covariance. An intention-to-treat approach will be used. Mixed-model repeated measures will be applied to explore effect of intervention across all time points. Ethics and dissemination: The study has received ethical approval (Dnr: 2016/14-31/1). The study findings will be disseminated through peer-reviewed publications, conferences and reports to key stakeholders. Trial registration number: NCT02914496 ; Pre-results.